آليات التّماسك النّصّي في الشّعر المقاوم: الإحالة والتّكرار في قصيدة لكِ الله يا غزّة الشّهداء لعبد الرّحمان أقرع - بحري قويدر (University of Eloued جامعة الوادي, 2025)
يتناول هذا البحث بعض آليات التّماسك النّصي في الشّعر السياسي المقاوم، حيث يركّز على الإحالة والتكرار وفاعليتهما في تعزيز التماسك النصي وانسجامه، إذ يقدّم قراءة تحليلية ودراسة تطبيقية لقصيدة "لكِ الله يا غزة الشهداء" للشاعر الفلسطيني عبد الرحمان أقرع، كما يهدف إلى الكشف عن كيفية توظيف هاتين الآليتين اللغويتين لتعزيز وحدة النص وانسجامه الداخلي، بما يخدم الرسالة النضالية التّحرّرية التي يحملها، ويرسّخ الدّلالات الثورية، و يبرز العلاقة بين البنية الشكلية والبنية الدلالية في القصيدة، ما يؤكّد دور الشّعر المقاوم كأداة فاعلة في الصحوة وإيقاظ الضمير العربي، وتعزيز تأثيره على المتلقي وتعميق الرّسالة الشعرية. Abstract: This study explores certain mechanisms of textual cohesion in political resistance poetry, focusing on the roles of reference and repetition in reinforcing the unity and coherence of the text. It presents an analytical reading and applied study of the poem "May God Be with You, Gaza of Martyrs" by Palestinian poet Abdelrahman Aqra'. The aim is to uncover how these two linguistic strategies are employed to strengthen the internal structure of the poem and serve its liberational and resistance message. The study also seeks to highlight how these elements reinforce revolutionary meanings and reveal the relationship between the poem’s formal structure and its semantic content. Ultimately, this confirms the role of resistance poetry as an effective tool for awakening Arab conscience and intensifying the impact of the poetic message on the recipient.
Textual Cohesion Mechanisms In Resistance Poetry: Reference And Repetition In The Poem "may God Be With You, Gaza Of Martyrs" By Abdelrahman Aqra'
مقال . القارئ للدراسات الأدبية و النقدية و اللغوية. مج 08. ع 02
Keywords: عبد الرحمان أقرع; الشعر المقاوم; التّحرر; غزة; الشهداء; العرب; Abdelrahman Aqra'; resistance poetry; liberation; Gaza; martyrs; Arabs